Antimicrobial policy interventions in food animal production in South East Asia - Goutard, Flavie Luce; Bordier, Marion; Calba, Clémentine; Erlacher-Vindel, Elisabeth; Góchez, Delfy; de Balogh, Katinka; Benigno, Carolyn; Kalpravidh, Wantanee; Roger, Francois; Vong, Sirenda (BMJ (Online), 2017)
Flavie Goutard and colleagues call for concerted multisectoral measures through stronger policies to combat antimicrobial resistance